BOUNDARY CONDITIONS OF ATLANTIC EOCENE OXYGEN MINIMUM ZONES - ANNE BOERSMA; ISABELLA PREMOLI SILVA (Rivista Italiana di Paleontologia e Stratigrafia, 2020)
Biserial heterohelicid foraminifera are paleohydrographic indices for open ocean oxygen minimum zones. Comparison of the depletion of biserial heterohelicid carbon isotope ratios with the carbon isotope contrast through the water column is used to describe the strength of Eocene oxygen minima. Combining stable isotope values and percentages of planktonic foraminiferal index species, we describe the following boundary condition for early, middle and latest Eocene oxygen minimum zones in the Atlantic Ocean. Early Eocene - low meridional and vertical thermal contrasts, reduced upwelling and circulation vigor in a moderately war m, stable thermospheric ocean accompany a poorly developed, spatially restricted oxygen minimum. Middle Eocene - invigorated upwelling, large vertical and spatial thermal contrasts caused by cooling at the bottom but not at the surface together with increased ventilation of the water column accompany a strong, widely developed oxygen minimum; and Late Eocene - in a psychrospheric ocean low meridional and vertical thermal contrasts, reduced equatorial upwelling and atmospheric circulation with decreased current circulation vigor correlate with a homogeneous mixed layer in which an oxygen minimum is poorly developed above the thermocline, but not at mid depths.